Hubungan Self-Disclosure dengan Kesepian pada Perempuan Dewasa Awal dalam Konseling berbasis ChatGPT - Silviana Nurhidayah; Sofia Tri Putri; Ghozali Ghozali (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine the relationship between Self-Disclosure and loneliness in early adult women in ChatGPT-based counseling. The quantitative approach used the Spearman correlation technique through the SPSS 27.0 for Windows program to determine the relationship between variables. The subjects in this study were 200 early adult female respondents aged 18-25 years. The instruments in the study were the self-disclosure scale and the loneliness scale of the UCLA Loneliness Scale Version 3. The correlation coefficient result of 0.374 (r = 0.374) indicates a sufficient and positive correlation level. Based on these results, the hypothesis is accepted and it is concluded that there is a relationship between self-disclosure and loneliness in early adult women in ChatGPT-based counseling.